GIS - based land suitability analysis using AHP for public parks planning in Kota Bharu, Kelantan / Khalilah Hassan, Izrahayu Che Hashim and Siti Syamimi Omar - Khalilah, Hassan; Izrahayu, Che Hashim; Siti Syamimi, Omar (2015)
Optimal locations for public facilities, such as public parks, are significant issues in the urban planning of Kota Bharu, Kelantan. Therefore, specifically, Kota Bharu, Kelantan was selected as the study area where the land suitability model was applied to determine suitable land for public parks. This study was carried out within the framework of an Analytic Hierarchy Process (AHP) as a multi-criteria evaluation approach by integrating it with the Geographic Information System (GIS). The IDRISI GIS package was used to calculate the weights based on four alternative scenarios. Computed composite weights were inserted into the spatial analysis function of the GIS and produced four scenarios of suitability maps, i.e.: (a) population density, (b) existing public parks, (c) industrial area and, (d) land availability. Hence, based on the analysis and findings made in this research, finding suitable locations using the land suitability model for future park development is highly helpful. The results can be useful in the planning of public facilities and future land use planning in Kota Bharu, Kelantan.